ANALYSIS OF GENOCIDE AS AN INTERNATIONAL CRIME: A REVIEW OF THE INTERNATIONAL AD HOC COURT AND THE INDONESIAN AD HOC COURT - Banjarani, Desia Rakhma; Febriansyah, Artha; Hervando, Frizky; Vladislavovic, Botvinkin Valeriy; Irawan, Benny (Tirtayasa Journal of International Law, 2025)
Genocide is an extraordinary crime that has occurred since the era of world war. However, legal provisions related to the punishment of this crime have only been regulated since 1994, namely during the era of the ad hoc International Criminal Court for Rwanda (ICTR). Based on the description of this background, it is necessary to study related issues: How is genocide an international crime? and what about the legal arrangements regarding genocide in the International Criminal Tribunal Statute for Rwanda and the Human Rights Court Act? This study uses normative research methods with a statutory approach. Genocide is considered the most serious because it involves the international community, which the ICC has regulated. Genocide was first regulated in legal regulations, namely the Statute of the International Criminal Tribunal for Yugoslavia and the Statute of the International Criminal Tribunal for Rwanda. The regulation of legal protection for victims of genocide crimes in Indonesia is expressis verbis contained in the provisions of Article 34 paragraph (1) of Law Number 26 of 2000 concerning the Human Rights Court. However, even though it has been controlled, the author has not found a standard procedure for victims to obtain their rights. This research gives contribution related to the differences in legal provisions between  the genocide provisions in the Statute of the International Criminal Tribunal for Rwanda as an international ad hoc court with the Law on Human Rights Courts.